Pemberdayaan Masyarakat Melalui Penyuluhan Hukum Tentang Legalisasi Industri Rumah Tangga Di Desa Bendungan - Erman I Rahim; Moh. Rusdiyanto Puluhulawa; Nuvazria Achir (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
The development of the home industry is currently increasingly stretched and is important for economic growth for the country. The more businesses, the more jobs. Micro, Small and Medium Enterprises (MSMEs) are also an important pillar in economic growth, so it is necessary to innovate to make it easier for MSMEs to carry out their roles and activities after the COVID-19 pandemic. However, its development still has obstacles, one of which is the difficulty in obtaining business legality and formality. The problem of MSMEs in the aspect of obtaining business permits and certification must be a serious concern, because the costs are relatively large and need assistance. Anticipating this requires a policy that is able to guarantee and protect business actors so that they can compete in the midst of global economic liberalization. This is experienced by MSMEs in Bendungan Village which consists of several business groups such as; Palm Sugar Producers, Pastries and Egg Nut Manufacturing Groups, who do not yet have legality such as a business license. Based on the existing problems, the solutions offered are specifically in Bendungan village, namely; Counseling on licensing and certification laws. The implementation of this counseling aims to provide understanding to the community, especially business actors to register their products so that they have legality and are recognized for their validity in the community. Not only that, training and Business Management Guidance were also carried out such as product packaging. Counseling was carried out in collaboration with the Office of Investment and Energy and Mineral Resources of Boalemo Regency as a resource person. The licensing process only needs to be done in a system (online) on the Online Single Submission (OSS) page by entering personal data in the form of the business owner's KTP and NPWP. Having a permit for this business makes it easier for people to market their products in supermarkets, and provides opportunities for people to get financial support from the government. While other activities are training in making packaging for community business products accompanied by students. Constraints faced by the community such as ownership of NPWP, it is suggested to the sub-district and village governments to hold a management and procurement program directly in the village to make it easier for the community. In addition, the village needs to map out the marketing locations for community business products and support packaging for the progress of the village, through economic empowerment in home industries.